2021
DOI: 10.3390/foods10081937
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Photoprotective, Anti-Inflammatory, Antioxidant Capacities and LC–ESI–MS Phenolic Profile of Astragalus gombiformis Pomel

Abstract: Plant-derived compounds have recently been gaining popularity as skincare factors due to their ability to absorb ultraviolet radiations and their anti-inflammatory, and antioxidant properties. In this light, this work aimed to evaluate in vitro the pharmacological activities of the butanolic extract prepared from the aerial parts of Astragalus gombiformis Pomel, an endemic species to southern Algeria. The sun protection factor was used to assess the photoprotective effect (SPF), the protein denaturation method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Similar to the present work, and by using LC–ESI–MS, it has been documented that the A. armatus ethanolic fraction contains quercetin and kaempferol in low concentrations [ 12 ]. It was also mentioned that the A. armatus ethanolic fraction produced through sample extraction contained significant levels of cirsiliol (37.1 ± 1 µg/g DM).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Similar to the present work, and by using LC–ESI–MS, it has been documented that the A. armatus ethanolic fraction contains quercetin and kaempferol in low concentrations [ 12 ]. It was also mentioned that the A. armatus ethanolic fraction produced through sample extraction contained significant levels of cirsiliol (37.1 ± 1 µg/g DM).…”
Section: Resultssupporting
confidence: 82%
“…Aromatic compounds and essential oils are found in several Astragalus species, with a variety of medicinal and economic applications [ 11 ]. The capacity of this species to inhibit the enzymes associated with a variety of chronic illnesses has been demonstrated by several studies [ 10 , 11 , 12 ]. It has been demonstrated that several bioactive substances from this genus are effective in cancer treatment [ 12 ], including saponins, which had a substantial anticancer impact on hamsters [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations